(3ebOeI aj GdEMUGA (B:s (3eaGgje h WQGFb (B/s - (3GdCTbQ, CMeO eUWais ((3YeGf(B: s (3OGQ GdKbGaI ddfTQ hGdJhRjY(B, s, 2020)
(3jVe gPG GdcJGH GdEMUGA hGdHjGfGJ GdEMUGFjI, ebGjjS GdJhVY GdeQcRj, ebGjjS GdJTJJ hebGjjS Tcd GdJhRjY, GdeONd Edi fXQjI GdEMJeGd, GdeJMhdGJ GdYThGFjI, GdYjfI, fXQjI GdJbOjQ,GNJHGQ GdaQVjGJ, GdYdGbI Hjf eJMhdjf GdEfMOGQ hGdEQJHGW, GSJYeGd GdMGShH aj eYGdLI GdeSGFd GdEMUGFjI(B.s
(3GdeQGLY U(B.350 (3GdcJGH Ydej heMce JfWHb Ydjg eYGjjQ GdHMK GdefThQs
Keywords: (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s; (3GdEMUGA GdhUajs